1991
DOI: 10.7883/yoken1952.44.147
|View full text |Cite
|
Sign up to set email alerts
|

MOLECULAR CLONING OF cDNA OF HEPATITIS C VIRUS (HCV) GENOME FROM A HEALTHY CARRIER IN AN ABORIGINAL COMMUNITY IN TAIWAN WITH HIGH PREVALENCE OF HCV INFECTION

Abstract: SUMMARY:We analyzed hepatitis C virus (HCV) obtained from a healthy HCV carrier in an aboriginal community with high prevalence of HCV infection. By use of random primers and specific oligonucleotide primers, a cDNA fragment of putative non-structural 3 (NS3) region of the HCV genome was cloned by reverse transcription-polymerase chain reaction (RT-PCR) using RNA extracted from a serum sample of a healthy HCV carrier in Taur-Yuan village. The nucleotide and deduced amino acid sequences from the 583 nucleotides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
1995
1995

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…DISCUSSION This study showed that 11 HCV strains isolated from hemodialysis patients were either of type II or type III. Until now in Taiwan, HCV strains isolated at several laboratories including ours were all of type II (13,18). This is the first report of type III HCV in Taiwan.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…DISCUSSION This study showed that 11 HCV strains isolated from hemodialysis patients were either of type II or type III. Until now in Taiwan, HCV strains isolated at several laboratories including ours were all of type II (13,18). This is the first report of type III HCV in Taiwan.…”
Section: Resultsmentioning
confidence: 58%
“…cDNA of HCV RNA was synthesized with random hexanucleotide primers and reverse transcriptase of Moloney murine leukemia virus. Afterward, the cDNA was subjected to PCR after adding a pair of specific NS5 primers (NS5-S, 5'-TGGGGATCCCGTATGATACCCGCTGCTTTGA-3'; NS5-A , 5'-GGCGGAATT-CCTGGTCATAGCCTCCGTGAA-3') by the procedure described previously (18). The sequences of the primers were quoted from the report by Enomoto et al (19) .…”
Section: Methodsmentioning
confidence: 99%
“…Hepatitis C virus (HCV) was first isolated by Choo et al [19891. The subsequent application of enzyme immunoassay (EIA) for circulating antibody to HCV using recombinant antigens has made it clear that HCV accounts for most cases of blood-borne non-A, non-B hepatitis Kuo et al, 1989;Bruix et al, 1989;Alter et al, 1989;Miyamura et al, 19901, and infects about 1% of the general population worldwide [Esteban et al, 1989;Stevens et al, 1990; van der Poel 0 1994 WILEY-LISS, INC. Wu et al, 19911. Further reports from Japan revealed difference of nucleotide sequences of Japanese isolates from that of the prototype virus isolated in the United States [Kato et al, 1989;Kubo et al, 1989;Kaneko et al, 1990;Maeno et al, 1990;Takeuchi et al, 1990a,b,c;Okamoto et al, 1990Okamoto et al, , 1991Takamizawa et al, 1991;Inchauspe et al, 1991;Enomoto et al, 19901, and it was known that patients in the United States and European countries are infected mostly with prototype HCV and the type isolated from Japan infects most of the victims in Asian countries [Chen et al, 1991;Chou et al, 1991;Takada et al, 1992;Okamoto et al, 1992a,b;Houghton et al, 19911. More recently, by comparing nucleotide sequence motif of domains, six genotypes of HCV are classified, and different genotypes are known to coexist in various geographical locations [Takada et al, 1992;Okamoto et al, 1992a;Cha et al, 1992;Kato et al, 1990;Chan et al, 1991;Mori et al, 19921. Recently, two rather simplified methods were developed for genotyping of HCV depending on: 1) the amplification of a C gene sequence by polymerase chain reaction (PCR) using a universal primer and a mixture of four type-specific primers based on variation in nucleotide sequence within restricted regions in the putative C gene of HCV, and 2) identification of restriction fragment l...…”
Section: Introductionmentioning
confidence: 99%
“…3a) [21][22][23][24], In all. nearly 12 viral proteins produced from this ORF of HCV lb, a major HCV genotype, have been iden tified thus far ( fig.…”
Section: Production Of H C V Proteins Via Co-and Posttranslational Prmentioning
confidence: 99%